The Implications of Naturalist Illustration Image Media on Early Childhood Learning Concentration and Motivation - Zainul Fajri; Rostanti Toba; Chusnul Muali; Maria Ulfah; Fatimatus Zahro (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood between the ages of 0 and 6 years experiences rapid growth and development. Children at this age have considerable potential that must be nurtured by providing essential knowledge, attitudes, and skills. Teachers are responsible for helping students reach their full potential through learning activities. One of them is creating exciting learning media that increases students' concentration and motivation. This study aims to adapt the use of naturalist illustration media to children's concentration and learning motivation. This research is a qualitative descriptive study using documentation, observation, and interviews. The results show that using realistic images can arouse children's curiosity, increase their focus, and encourage learning through activities and consequences. Based on the findings of this study, it can be concluded that the use of naturalist images is very suitable for early childhood education, as evidenced by the increase in children's attention and learning motivation